Preventing infectious diseases outbreaks at exercise facilities. Issue 1 (4th March 2022) - Amagasa, Shiho; Machida, Masaki; Ding, Ding; Inoue, Shigeru
ABSTRACT: Exercise facilities play an important role in enhancing physical fitness and in supporting an active lifestyle among users. During the global coronavirus disease 2019 (COVID-19) pandemic, exercise facilities have been shut as part of the "physical distancing" policies in many countries. Exercise facilities have been considered "high-risk" places for transmission because of their enclosed environment, shared equipment and the close contact between users and staff. In Japan, in response to the COVID-19 clusters developed from the exercise facilities in the early phase of pandemic, the Fitness Industry Association of Japan released guidelines for gym managers, workers, and users in March. This commentary aims to introduce exercise facilities guidelines in Japan. This article provides reference for the rest of the world to reopen exercise facilities safely in the post pandemic period or to prevent future outbreaks of infectious disease.